Diospyros kaki Cr. and Climate Changes - Creveld, Marijke (Homœopathic Links, 2018)
Diospyros kaki Cr. as a homeopathic remedy was made from the Kaki tree from Nagasaki, Japan, that survived the 1945 Plutonium bomb attack on the city during the war between Japan and the USA. Two short cases show the remedy can be used for climate change–related indications, namely skin cancers and post-traumatic stress disorder.
Keywords: Diospyros Kaki Creveld; survival; safety; radiation; fire; PTSD